Reconstrução e crítica em Axel Honneth - Luiz Philipe Rolla de Caux (2015)
The present work reconstitutes the conceptual determinations of Axel Honneth's reconstructive model of critical theory through the history of its emergency. In order to place a problem, it deals initially (I.1 and I.2) with the first proposition by Habermas of the reconstruction as an adequate model to a critical theory of society considering the social transformations diagnosed in his time. The problems Habermas faced and especially his solutions throw a new light ahead in Honneth's further formulation of a distinct reconstructive model. Then Honneth refuses in such a way the diagnosis of time underlying Habermas' formulation, the basic concepts of his theory and, as this work shows, also the determinations of method of the habermasian reconstruction (I.3), that the consistency of Honneth's filiation in 1992 to the reconstructive model turns out to be not so obvious. Despite this, the work tries to demonstrate this consistency, inquiring what kind of modulation the reconstruction had to suffer in order to free itself from Honneth's indicated sociological deficit. The work maintains the hyposthesis that the first modulation given to the reconstruction is a link between genesis and validity of social normativity, separated by Habermas, and a focus shift of the research from the rational validity to the historical genesis: the first could only be thought from the latter (I.4). This modulation happens implicitly and with no further considerations of method in The Struggle for Recognition. It is prepared however by the difuse development of a concept of the social able to solve the mentioned sociological deficit (II.1). The Struggle for Recognition reconstructs the reconstruction itself from the young Hegel and then executes a "reconstruction from the point of view of the social" (Nobre) (II.2). The work shows however that the outcome of this first reconstruction, the tense concept of "formal ethical life", keep apart reconstruction and critique in two distinct moments and does not overcome one of the severe deficits which Honneth pointed out in Habermas considering the goals of a critical theory of society (II.3). In light of this new problem, Honneth's reviews of his theory in the 2000's are recoverd and sistematized. Honneth recasts from the beginning his compreension of intersubjectivity and shifts the reference of Hegel's writings from Jena to Berlin (III.1). He prepares the ground so to a reelaboration of a mature model able to unify in one moment reconstruction and critique. Honneth calls this in his The Right of Freedom the model of "normative reconstruction" (III.2). In conclusion and in an attempt of immanent criticism, the work suggests the limits of normative reconstruction in its inability to explain social pathologies.